Bibliometric and visualized analysis of elite controllers based on CiteSpace: landscapes, hotspots, and frontiers - Yuan, Xingyue; Lai, Yu (Frontiers in Cellular and Infection Microbiology, 2023)
Background: A unique subset of HIV-1-infected individuals, known as elite controllers, possess spontaneous and consistent control over viral replication and disease progression in the absence of any antiviral intervention. In-depth research on them is conducive to designing better treatment strategies. However, a comprehensive and illuminating bibliometric report on elite controllers is rare. Methods: Articles on elite controllers were retrieved from the Web of Science Core Collection. Visualized analysis of this domain was conducted by CiteSpace software. Taking count, centrality and burst value as criteria, we assessed the visualization results and predicted future new directions and emerging trends. Results: By December 31, 2022, a total of 843 articles related to elite controllers had been published. The largest contributors in terms of country, institution, and author were the United States (485), Univ Calif San Francisco (87), and Walker B.D. (65), respectively. Migueles S.A. (325) and Journal of Virology (770) were the most cocited author and journal, respectively. Additionally, by summarizing the analysis results of references and keywords, we considered that the research hotspots and frontiers on elite controllers mainly focus on three aspects: deciphering the mechanisms of durable control; delineating the implications for the development of treatments for HIV infection; and highlighting the clinical risks facing elite controllers and coping strategies. Conclusion: This study performed a bibliometric analysis of elite controllers, identified the main characteristics and emerging trends of this field, and provided insightful references for further development.